A short review on the utilization of pozzolan material in concrete - Shuhaimi, Shaedon; Azrina, Abd Aziz; Rahimah, Embong (Penerbit UMP, 2024)
This paper provides a short review on the agricultural waste and industrial waste as pozzolan material in concrete. The pre-treatment method, characterization process and the engineering properties of a suite of pozzolans used including rice husk ash (RHA), corn cob ash (CCA), sugarcane bagasse ash (SCBA), bamboo leave, oil palm shell (OPS), and others was studied. From the study, the agricultural waste which is Oil Palm Shell is highlighted to be use as pozzolan material in concrete apart for other used. Oil Palm Shell (OPS) ash as one of the agricultural based pozzolan gained less popularity due to its relatively low amorphous silica content after incineration process (< 50% silica). Therefore, an alternative approach was studied form the previous researcher to extract high proportion of amorphous silica from OPS ash that fulfils the minimum requirement of pozzolanic standard.